Usaha KH. As’ad Humam Dalam Pembaruan Sistem Pengajaran Baca Al-Qur’an - Annuri, Ahmad; Bahruddin, Ending; Saefudin, Didin (Ta'dibuna: Jurnal Pendidikan Islam, 2014)
The Qur’an is guidance, a light that illuminates human’s life from darkness, a beacon to the righteous way. Therefore, it is a necessity for all Muslims to learn the Qur’an, how to read it correctly, to comprehend it, to act upon it, and to spread it to others. The statistic tells that Indonesian Muslims are large in number but very low in their quality of interaction with the Qur’an. It is very sad to know. This situation is caused by: 1) less number of young people who are interested in becoming Qur’an teacher; 2) low quality of Qur’an teacher itself; 3) unprofessional management; 4) static development in the field of Qur’anic reading; 5) progress in technology and electricity that creates distraction among people; and 6) limited support from the government. Obstacles in the field of Qur’anic learning have brought new ideas and efforts to restructure new methodologies since 1980’s. One of the scholars in the field is KH. As’ad Humam from Kotagede, Yogyakarta, a low profile, generous, socialized, diligent, attentive guru, who has made teaching Qur’an as his main focus in life. His ideas and thoughts have delivered a new system and metoda of Qur’anic reading in Indonesia and the nearby countries. For example, even Malaysia has chosen Iqra’’, KH. As’ad Humam’s method, as their curriculum in their elementary level of Qur’anic reading. This research uses qualitative approach. Historical method in biography as well as bibliography is applied. The research was conducted from Mei 2011 to July 2012, located in Yayasan Team Tadarus AMM Yogyakarta and other locations as needed. The data were collected through indepth interview, document analysis, and observation. Data analysis is presented in descriptive quantitative. The finding in this research is a new system of teaching Qur’anic reading, contains 3 (three) main results: 1) ideas to create new method of teaching Qur’anic reading; 2) efforts to implement the new system/ method; and 3) efforts to spread the new system to people. This research has produced new theories: 1) the next sequel of Iqra’’ (ie. Iqra’ volume 7) to cover problems discovered during the teaching of Iqra’ 1-6; 2) a guidance to correct Qur’anic reading for excellent readers; and 3) a guidance using Irama Rost and Nahwan for excellent readers. These theories has become a new formula in teaching Qur’anic reading, that also serves to complete KH. As’ad Humam’s efforts. Keywords: As’ad humam, Sistem Pengajaran, Pembaharuan, Pengajaran al-Qur’an